Morphological and in vitro antibacterial efficacy of quercetin loaded nanoparticles against food-borne microorganisms. (March 2016) - Dinesh Kumar, V.; Verma, Priya Ranjan Prasad; Singh, Sandeep Kumar
Abstract: Biodegradable nanoparticles have been used regularly as drug delivery carriers owing to its bioavailability augmentation, better entrapment, sustained release and biocompatibility. The present study aimed to compare the antibacterial efficacy of quercetin loaded nanoparticles (QLNs) with free quercetin against Bacillus subtilis, Escherichia coli, Staphylococcus aureus, and Salmonella typhimurium (food-borne microorganisms). Stability study confirmed insignificant variation in particle size, zeta potential and encapsulation efficiency over a period of 90 days of storage. High resolution-transmission electron microscopy (HR-TEM) showed the formation of spherical nanoparticles with smooth surface. The antibacterial activity of free quercetin and QLNs were evaluated for zone of inhibition, percentage retardation of bacterial growth, kinetic measurement, minimum inhibitory concentration and minimum bactericidal concentration studies. The results indicated that QLNs were more efficient than free quercetin owing to control release of quercetin from nanoparticles. The mechanism of antibacterial activity of QLNs was investigated by atomic force microscopy and scanning electron microscopy. Microscopic study revealed the adsorption of nanoparticles on bacterial cell surface followed by increased cell permeability causing cell lysis. Highlights: Nanoencapsulation of bioactives increases drug efficacy, specificity, tolerability and therapeutic index. Stability studies construed stability of QLN more than 90 days. Microtiter bioassay was used for quantitative antibacterial assessment. QLN promotes the sustained release and superior antibacterial activity than free drug. AFM and SEM studies were confirms the antibacterial action of QLN against tested bacterial cells.